The Rationality of West Sumatra RPJPD Targets 2025-2045: An Analysis of Science, Technology, Innovation, and Economic Productivity Goals - Zul Ammar; Sri Maryati (Transpublika Publisher, 2025)
This study analyzes the rationality of development targets outlined in the West Sumatra RPJPD 2025-2045, focusing on goals in the fields of science and technology (IPTEK), innovation, and economics. The indicators examined include the manufacturing industry GDP ratio, tourism development, creative economy, MSME productivity, entrepreneurship, BUMD performance, formal job creation, female labor force participation, and regional innovation index. The analysis reveals that some targets, such as the non-agricultural MSME GDP proportion and female labor force participation, are considered realistic as they align with historical trends. However, other targets, such as the manufacturing industry GDP ratio, tourism development, and entrepreneurship, are deemed highly ambitious as they require growth rates far exceeding historical averages. Achieving these targets will require progressive policies, significant investments, and synergy between the government, society, and the private sector. This study provides critical insights for evaluating the realization of future development targets.